Hydrozirconium reaction in heterogeneous compositions - V.K. Milinchuk; E.R. Klinshpont; V.I. Belozerov; A.V. Zagorodnyaya (Nuclear Energy and Technology, 2017)
The research results presented in this article show the behavior of a hydrozirconium reaction for hydrogen generation at temperatures below 100°C in heterogeneous compositions containing zirconium and chemical activators (e.g., hydrated sodium metasilicate, sodium water glass, or quicklime). The hydrogen yield increases with a temperature increase up to 95°C and is about 0.1–0.2l per 1g of zirconium. Zirconium processing with γ-radiation as well as exposure to acidic and neutral aqueous media increases the hydrogen yield by about 1.2 times. A hydrozirconium reaction is caused by the chemical activators removing the passivating protective zirconium oxide ZrO2 layer from the metal surface. The possibility of a hydrozirconium reaction occurrence should be considered in the organization of technical measures to ensure hydrogen explosion protection at NPPs.